2011
DOI: 10.1007/s11069-011-9801-0
|View full text |Cite
|
Sign up to set email alerts
|

Risk perception and evacuation decisions of Florida tourists under hurricane threats: a stated preference analysis

Abstract: Though most hurricane evacuation studies have focused on residents, tourists are also a vulnerable population. To assess their perceptions of risk and evacuation likelihood under different hurricane conditions, we surveyed 448 tourists visiting central Florida. Respondents viewed four maps emulating track forecast cones produced by the National Hurricane Center and text information featuring variations of storm intensity, coast of landfall, centerline position relative to the survey site, time until landfall, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
69
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 104 publications
(76 citation statements)
references
References 53 publications
6
69
0
1
Order By: Relevance
“…When comparing the mean score of males and females, the mean score for females (2.5357) was found to be higher than the males (2.4603) as shown in table 5, which suggests that females had higher risk perception as compared to the males. Most literature has also found that females are more risk averse than males (Lepp & Gibson, 2003;Matyas, et al, 2011;Pizam, et al, 2004). Therefore, it is assumed that the females perceive more risk as compared to the male respondents.…”
Section: One Way Anova and Independent Samples T-testmentioning
confidence: 99%
“…When comparing the mean score of males and females, the mean score for females (2.5357) was found to be higher than the males (2.4603) as shown in table 5, which suggests that females had higher risk perception as compared to the males. Most literature has also found that females are more risk averse than males (Lepp & Gibson, 2003;Matyas, et al, 2011;Pizam, et al, 2004). Therefore, it is assumed that the females perceive more risk as compared to the male respondents.…”
Section: One Way Anova and Independent Samples T-testmentioning
confidence: 99%
“…Research has been conducted on the attitudes of different populations when encountering extreme events prompting evacuations, with most of the data available related to hurricane evacuations. A study in Florida [18] took survey data and found that people make a decision to evacuate or shelter in place based on the perception of the negative impact of the threat and likelihood of their residence being in harm's way. The study found that the higher the risk the more likely citizens are to evacuate.…”
Section: Communicating To the Public During Evacuationsmentioning
confidence: 99%
“…Transient populations such as tourists have received minimal attention Matyas et al, 2011;Villegas et al, 2013). The few noteworthy contributions to tourist behavior during hurricanes were published in the early and mid1990s and largely by one author (Drabek, 1994;1995;1996b; with a focus on evacuation strategies and policies.…”
Section: Introductionmentioning
confidence: 99%
“…The few noteworthy contributions to tourist behavior during hurricanes were published in the early and mid1990s and largely by one author (Drabek, 1994;1995;1996b; with a focus on evacuation strategies and policies. Only recently has research been conducted which explores the viewpoints of tourists Matyas et al, 2011;Villegas et al, 2013).…”
Section: Introductionmentioning
confidence: 99%